A possible trigger for a wave-function collapse - Cordin, Michael (Frontiers in Physics, 2022)
The measurement problem is usually analysed with the quantum decoherence or wave-function collapse theory. Both theories seem to be equivalent with respect to experiments. The trigger/reason for a wave-function collapse is not clearly defined (in the corresponding theory) and the present work is an attempt to close this gap. The present thought experiment describes a measurement to determine the localization of an electron inside a box. The present work assumes that the determination of information (about the localization of the electron) induces a wave-function collapse. It seems possible to identify a clearly defined trigger for a wave-function collapse in the described model system.